Assessing Quality of Care in the Kyrgyz Republic : Quality Gaps and Way Forward - Ahmedov, Mohirjon (World Bank, Washington, DC, 2020)
Systematic assessments of the quality of care provide a platform for taking stock of achievements, identifying gaps, and having an informed discourse on the way forward. However, data-driven comprehensive assessments of the state of quality in the Kyrgyz Republic are lacking, despite much anecdotal evidence on poor quality of care. This report will be the first attempt at bringing together different datasets and sources of information to provide a comprehensive data-driven view of the state of quality in the country, with international benchmarking of the Kyrgyz data as and when appropriate. This report will describe the socioeconomic context in the country with a focus on health financing and outcomes in its first chapter. In the second chapter, the current state of quality in the Kyrgyz Republic will be evaluated using the quality measurement framework proposed by Donabedian. Findings from the assessment will inform key conclusions and policy recommendations in the final chapter of the report.